In-depth characterization of the neuroinflammatory reaction induced by peripheral surgery in an animal model - Plaschke, Konstanze; Weigand, Markus A.; Kopitz, Jürgen (Journal of neural transmission, 2018)
Delirium is a common complication seen after surgery and anesthesia, in particular in older patients. Although the etiology of postoperative delirium is only incompletely understood, various lines of evidence suggest that proinflammatory signaling from the peripheral site of inflammation to central nervous system results in a decrease of cerebral acetylcholine (ACh) levels thereby inducing neuroinflammation. To corroborate this theory, we applied an animal model for characterization of the neuroinflammatory response after partial hepatectomy (HPx).